Impact of WaSH Practices on Stomach-Related Diseases in Indian Households : A Public Policy Perspective - Sarna, Kamaldeep Kaur; Kaur, Simrit (Arthshastra Indian Journal of Economics & Research, 2024)
Purpose : Water, Sanitation, and Hygiene (WaSH) play a pivotal role in fostering inclusive growth and sustainable development. The global economic, social, and environmental repercussions of poor WaSH facilities are substantial, with developing countries bearing the major brunt. In this context, the present study examined the impact of WaSH practices on the prevalence of stomach-related diseases among Indian households. Methodology : Using data from the National Sample Survey 76th round, the study employed cross-tabulations and binary logistic regression to empirically investigate the correlates of health outcomes in India. Findings : A significant relationship between poor WaSH conditions and a higher incidence of stomach-related illnesses was found. Further disparities across socioeconomic settings highlighted the disproportionate impact of WaSH practices prevailing among the vulnerable sections. Notably, lower education levels, involvement in informal sector occupations, unimproved water sources, insufficient water availability, poor sanitation facilities, and inefficient water treatment methods significantly increased the likelihood of stomach ailments. Practical Implications : Providing safe and sufficient WaSH access should be prioritized by expanding WaSH infrastructure, strengthening water treatment facilities, promoting affordable household filters, facilitating regular quality inspections, and mandating proper housing and ventilation standards. Targeted interventions should be designed for marginalized groups by providing subsidized facilities and educating households across formal and informal settlements. Technological innovations and cross-sector collaborations should be leveraged for the successful implementation of the initiatives. Originality : The present paper contributed to the scant literature wherein the influence of WaSH practices on Indian households’ well-being was investigated. Further, the impact of both demographic and contextual variables was analyzed, providing valuable policy insights.